THE IMPACT OF PROJECT MANAGEMENT ON THE EFFICIENCY OF IMPLEMENTING INNOVATIVE BANKING PRODUCTS AND SERVICES (American Journal of Business Management, Economics and Banking, 2024)
This article analyzes the correlation between the project management methodologies used and the final results of innovation implementation in banking structures. The study systematizes key success factors and identifies potential risks associated with the implementation of such projects. Based on the theoretical analysis and practical experience, a conclusion is reached regarding the high feasibility of using hybrid project management models in the development and integration of innovative banking solutions.